Using PhET Simulations and Differentiated Instruction to Improve Ninth-Grade Students’ Understanding of Physics Concepts - Nurul Ilmiyah; Kuncahyono Kuncahyono; Agus Tinus (Journal of General Education and Humanities, 2026)
This study aimed to analyze the effectiveness of integrating PhET simulation media with differentiated instruction in improving students' understanding of physics concepts among ninth-grade students at SMP Muhammadiyah 1 Gresik, focusing on dynamic electricity. The study was motivated by students’ limited conceptual understanding resulting from the abstract nature of physics concepts and the lack of adaptive instructional strategies that accommodate diverse learning needs. A mixed-methods approach with a sequential explanatory design and a quasi-experimental one-group pretest–posttest design was employed. The participants consisted of 68 ninth-grade students in the 2025/2026 academic year. Quantitative data were collected through pretest and posttest assessments, whereas qualitative data were obtained from classroom observations and interviews. Quantitative data were analyzed using normalized gain (N-gain) and a paired-samples t-test, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The findings showed that the intervention effectively improved students’ understanding of physics concepts. The mean score increased from 57.51 on the pretest to 77.18 on the posttest, with an average N-gain of 0.42, indicating moderate improvement. Most students achieved moderate to high learning gains, and qualitative findings revealed that integrating PhET simulations with differentiated instruction enhanced students’ engagement, motivation, exploratory learning, and conceptual retention across different levels of prior ability. These findings suggest that integrating PhET simulations with differentiated instruction offers an adaptive, innovative approach to improving students’ understanding of physics concepts.